Reconnaissance et Validation des Acquis de l´Expérience. Les résultats (in)attendus - Carmen Cavaco (Université de Provence, 2013)
The aim of this text is to analyze the results of the process of recognition and validation of non-formal and informal learning in the adults certified. Empirical data was collected by interviews with three teams responsible for this process and by biographical interviews of fourteen certified adults. The data analysis, supported in the theoretical elements of Educational Science, allowed to identified a paradox. The policy guidelines did not include the training of adults but simply obtaining their educational diploma. However, the adults interviewed confirmed the importance of the realization of this process in their learning. The adults learned in this process due to accessing their experiences and their knowledge.